HUBUNGAN ANTARA SELF TALK DENGAN KEPERCAYAAN DIRI PADA ATLET BOLA BASKET DI KOTA PALEMBANG - Tifani, Tifani (Jurnal Ilmiah Psyche, 2015)
This study aims to determine the relationship between of self regulation with academic procrastination in the student guidance and counseling courses semesters 4 and 6 of PGRI university Palembang. The hypothesis proposed in this study is there a relationship between self regulation with academic procrastination in the student guidance and counseling courses semesters 4 and 6 of PGRI university Palembang. The results by using SPSS version 20.0 showed a correlation coefficient (r) of0,603 with a coefficient of determination (R-square) of 0,364, and p = 0,000 p < 0.01. This suggests that the hypothesis is accepted which showed that there is a significant relationship betweenself regulation with academic procrastination in the student guidance and counseling courses semesters 4 and 6 of PGRI university Palembang